2015
DOI: 10.1542/peds.2015-1099
|View full text |Cite
|
Sign up to set email alerts
|

Interpregnancy Interval and Risk of Autism Spectrum Disorders

Abstract: OBJECTIVE: To determine whether subsequent births after short and long interpregnancy intervals (IPIs) are associated with risk of autism spectrum disorder (ASD). METHOD:We assessed the association between IPI and ASD risk in a cohort of 45 261 children born at Kaiser Permanente Northern California (KPNC) between 2000 and 2009. Children with ASD were identified from International Classification of Diseases, Revision 9 diagnostic codes 299.0, 299.8, and 299.9 recorded in KPNC electronic medical records. IPI was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
50
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 38 publications
5
50
1
1
Order By: Relevance
“…32 However, a sensitivity analysis restricted to individuals with more severe ASD revealed a significant association between IPIs of <12 months and this disorder. Three studies also found a significant association between ASD and long IPIs (≥60 months, 31 ≥72 months, 34 and ≥84 months 33 ). Five studies reported a significantly increased risk of the former subtype autistic disorder associated with short IPIs.…”
Section: Autism Spectrum Disordermentioning
confidence: 90%
See 4 more Smart Citations
“…32 However, a sensitivity analysis restricted to individuals with more severe ASD revealed a significant association between IPIs of <12 months and this disorder. Three studies also found a significant association between ASD and long IPIs (≥60 months, 31 ≥72 months, 34 and ≥84 months 33 ). Five studies reported a significantly increased risk of the former subtype autistic disorder associated with short IPIs.…”
Section: Autism Spectrum Disordermentioning
confidence: 90%
“…28,31,33 However, long IPIs were found to be associated with an increased risk of the former subtypes Asperger disorder and PDD-NOS in 3 studies. 31,33,34 Overall, there was no association between short IPIs and the risk of these 2 disorders. 30,31,33,34 Table 2 shows the meta-analyses of the association between IPI and ASD.…”
Section: Autism Spectrum Disordermentioning
confidence: 92%
See 3 more Smart Citations